La Tirana. Marian Cult in the Atacama Desert of the Large Northern Zone of Chile - Guerrero, Bernardo (Revista de Estudios Andaluces, 2021)
In this work we reflect on the relationships established between popular religiosity and the Atacama Desert in the Norte Grande of Chile. For this we see how that immense territory that is the desert is perceived by the political, military and ecclesial elites. First as a place lacking of life and second as sources of wealth, especially minerals. The festival of La Tirana and its vast pilgrimage has caused the sacralization of some of its parts. What was a non-place was transformed into a place full of meaning. Popular religiosity is, as we shall see later, a territorial inscription. In methodological terms, we have made long trips to this festival for more than a decade, an observation and interpretation from the pilgrims’ point of view. Long conversations, analysis of the religious songbook, among others, constitute our empirical sources. We conclude that thanks to the pilgrimage the desert of being conceived as something empty, is filled with life.